IMPORTANCE OF GRANTING TO THE CONSTITUTIONAL COURT OF GEORGIA THE AUTHORITY OF CONSIDERING THE “REALISTIC” CONSTITUTIONAL APPEALS - Kuchukhidze, Ana (The Copernicus Journal of Political Studies, 2018)
On the basis of the current legislation in relation to the issues of the second chapter of the Constitution (Human rights), the Constitutional Court of Georgia considers only the issue of the constitutionality of the content of normative acts and considers the appeals as inadmissible where the violation of rights is derived not from the content of the norm but its misuse in practice. This approach extends as well to those cases when the violation of a person’s rights is caused by incorrect interpretation of the norm by the court and improper use in the process of legal correlation. The Georgian Legislation does not grant to the Constitutional Court the authority to consider the indicated issue. The indicated issue is a legal problem to the extent that the initial point of the democratic states is to defend the human rights and correspondingly, the primary goal of the constitutional control should be the restoration of the human rights violated by the state structures (authorities). However, the recent precedential law gives us a possibility to make the conclusion that the General Courts in a number of cases define the law contrary to the Constitution, and the Constitutional law is powerless to restore the right of the person whose right was violated by the action of the judge of the court. The aim of this article is to analyze advantages and disadvantages of real-life constitutional appeals and prove importance of granting to the Constitutional Court of Georgia the authority of considering the “realistic” constitutional appeals.